An investigation of the genetic correlation of 200-, 400-, and 600- day weights between beef-on-dairy and beef calves : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatū, New Zealand - McFarlane, Connie Elizabeth (Massey University, 2024)
The expansion of the New Zealand dairy industry has led to an increase in the number of lower-value surplus calves. A mitigation strategy to increase the value of surplus calves is to have them enter the beef market. The aim of this thesis was to investigate the genetic connection between values generated in the dairy-beef progeny test and those generated by the beef progeny test. This was achieved, in part, by researching the genetic correlation between dairy weaning weight, 200-, 400- and 600-day weights in beef-on-dairy compared to beef calves. The data required for the research was collected in the National Dairy-Beef progeny test and the National Beef progeny test funded by Beef+Lamb NZ. Least squares mean for weaning weight, 200-day weights, 400-day weights and 600-day weights were obtained using a generalised linear model. A single-trait animal model was used to estimate genetic parameters, variance components and calculate heritabilities. A bivariate animal model was also used to estimate the genetic and phenotypic correlations between variables. The estimated heritabilities for beef-on-dairy cattle were lower than those generated from beef cattle, in particular, weaning weight (0.17 vs. 0.67) and 200-day weight (0.43 vs. 0.78). This difference may be due to maternal effects, management system differences and the focus of breeding programmes. The heritabilities for 400-day and 600-day were high in both beef and beef-on-dairy cattle, therefore, indicating that these traits are under greater genetic influence. The genetic correlations for growth traits were strong (ranging between 0.60 and 0.96) while the phenotypic correlations were generally lower than the genetic correlations (0.26 and 0.83) within beef cattle and beef-on-dairy cattle. Given these results, the study recommends using beef progeny tests to predict growth traits for both beef and beef-on-dairy systems. This will simplify the breeding process, reduce costs and will enhance the genetic merit of the calves entering the beef industry.
Keywords: 300301 Animal growth and development